WORKING STATUS, SOCIAL EATING AND DIET QUALITY AMONG THE INDONESIAN PRODUCTIVE-AGE POPULATION: A STUDY OF THE INDONESIAN FOOD BAROMETER - Rahma, Alkanisa; Khusun, Helda; Kamila, Indah Tasya; Februhartanty, Judhiastuty (Media Gizi Indonesia, 2025)
The 2014 Total Diet Study reported that the dietary patterns among Indonesians remain inconsistent with the 2014 Balanced Nutrition Guidelines. Employment status is known to influence social eating behaviors, and social eating during lunch may affect diet quality. This study aims to determine the relationship between employment status and social eating with diet quality among the productive-age population in Indonesia as measured by the Balanced Nutrition Index. This study employed a cross-sectional approach using secondary data from the 2018 Indonesian Food Barometer, with a sample of 271 respondents (135 men and 136 women) who met the inclusion criteria. The variables analyzed in this study were respondent characteristics, employment status, and social eating. Chi-squared test revealed that employment status and social eating had no significant relationship with diet quality. However, socioeconomic status had a relationship with diet quality (p = 0.026). Multivariate analysis further revealed that socioeconomic status was a dominant factor in diet quality among the productive-age population in Indonesia. Individuals with low socioeconomic status faced a 2.5-times higher risk of poor diet quality compared to those with high socioeconomic status.